A novel sequential process for remediating rare-earth wastewater. (February 2016) - Cui, Mingcan; Jang, Min; Kang, Kyounglim; Kim, Dukmin; Snyder, Shane A.; Khim, Jeehyeong
Abstract: A novel and economic sequential process consisting of precipitation, adsorption, and oxidation was developed to remediate actual rare-earth (RE) wastewater containing various toxic pollutants, including radioactive species. In the precipitation step, porous air stones (PAS) containing waste oyster shell (WOS), PASWOS, was prepared and used to precipitate most heavy metals with >97% removal efficiencies. The SEM-EDS analysis revealed that PAS plays a key role in preventing the surface coating of precipitants on the surface of WOS and in releasing the dissolved species of WOS successively. For the adsorption step, a polyurethane (PU) impregnated by coal mine drainage sludge (CMDS), PUCMDS, was synthesized and applied to deplete fluoride (F), arsenic (As), uranium (U), and thorium (Th) that remained after precipitation. The continuous-mode sequential process using PASWOS, PUCMDS, and ozone (O3 ) had 99.9–100% removal efficiencies of heavy metals, 99.3–99.9% of F and As, 95.8–99.4% of U and Th, and 92.4% of CODCr for 100 days. The sequential process can treat RE wastewater economically and effectively without stirred-tank reactors, pH controller, continuous injection of chemicals, and significant sludge generation, as well as the quality of the outlet met the EPA recommended limits. Graphical abstract: Highlights: A novel sequential process was developed to treat rare-earth (RE) wastewater. PASWOS removed most heavy metals with >97% efficiencies in the precipitation step. PAS plays a key role in releasing sequentially the dissolved species of WOS. PUCMDS removed fluoride, arsenic, uranium, and thorium that remained after precipitation. Continuous sequential process successfully depleted all pollutants for 100 days.